Finances of Egyptian Listed Firms - Love, Inessa (World Bank, Washington, DC, 2012)
The author presents an analysis of the finances of Egyptian listed companies evaluating recent trends in growth and profitability during the 1995-2001 period. The data from financial statements reveal the effect of the economic slowing of the past few years, especially in the construction and real estate sectors and especially in smaller companies. She finds that smaller firms appear to be less profitable and experience lower growth, likely because of being particularly adversely affected by many of the sources of the high costs of doing business in Egypt. While the Egyptian firms are not very highly leveraged on average, she finds that smaller firms have significantly less access to bank finance than larger firms do. This confirms the widely held view that there is a need to improve the availability of credit for small enterprises.